Band Time-Domain Multiplexing FMCW MIMO Radar for Far-Field 3-D Imaging - Bleh, Daniela; Rosch, Markus; Kuri, Michael; Dyck, Alexander; Tessmann, Axel; Leuther, Arnulf; Wagner, Sandrine; Weismann-Thaden, B.; Stulz, H.-P; Zink, Martin; Riessle, M.; Sommer, R.; et al. (IEEE transactions on microwave theory and techniques, 2017)
In this paper, a radar demonstrator system with real-time capability operating at W -band is presented. It operates at 90-100 GHz and provides 3-D information about the illuminated scene. The system uses frequency modulated continuous wave signals to extract range information whereupon long-range applications are aimed at. It consists of a sparse array of 22 transmitting and 22 receiving antennas and makes use of the multiple input multiple output (MIMO) principle. A back-propagation algorithm provides cross-range information. With the help of simulations and a simulated annealing algorithm, the geometry of the sparse array is optimized to meet application requirements using the available hardware. In this paper, the demonstrator system is described and the imaging theory is shortly reviewed. Measurements are presented to verify simulation results as well as 3-D imaging and long-range capability.